Bangladesh : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2006)
This Joint Staff Advisory Note provides IMF staff advice on key priorities for strengthening Bangladesh's poverty reduction strategy (PRS) and for ensuring its effective implementation. It highlights key strengths of the PRS while bringing out some weaknesses of existing policies that may undermine successful implementation of the strategy. The note highlights that the strategic agenda of the National Strategy for Accelerated Poverty Reduction (NSAPR), built on the policy triangle of pro-poor growth, human development, and governance, is consistent with the challenge of accelerating growth and poverty reduction.